Pelvic and reproductive structures in placoderms (stem gnathostomes) - Trinajstic, Kate; boisvert, C.; Long, J.; Maksimenko, A.; Johanson, Z. (Wiley-Blackwell Publishing Ltd., 2014)
Newly discovered pelvic and reproductive structures within placoderms, representing some of the most crownward members of the gnathostome stem group and the most basal jawed vertebrates, challenge established ideas on the origin of the pelvic girdle and reproductive complexity. Here we critically review previous descriptions of the pelvic structures in placoderms and reinterpret the morphology of the pelvic region within the arthrodires and ptyctodonts, in particular the position of the pelvic fin and the relationship of the male clasper to the pelvic girdle. Absence of clear articular surfaces on the clasper and girdle in the Arthrodira, along with evidence from the Ptyctodontida, suggest that these are separate structures along the body. We describe similarities between the pectoral and pelvic girdles and claspers, for example, all these have both dermal and perichondral (cartilaginous) components. Claspers in placoderms and chondrichthyans develop in very different ways; in sharks, claspers develop from the pelvic fin while the claspers in placoderms develop separately, suggesting that their independent development involved a posterior extension of the 'competent stripes' for fin development previously limited to the region between the paired pectoral and pelvic fins. Within this expanded zone, we suggest that clasper position relative to the pelvic fins was determined by genes responsible for limb position. Information on early gnathostome reproductive processes is preserved in both the Ptyctodontida and Arthrodira, including the presence of multiple embryos in pregnant females, embryos of differing sizes and of different sexes (e.g. male claspers preserved in some embyros). By comparison with chondrichthyans, these observations suggest more complex reproductive strategies in placoderms than previously appreciated.